2021
DOI: 10.1515/phon-2021-2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal coordination in word-medial stop-lateral and s-stop clusters of American English

Abstract: This paper is concerned with the relation between syllabic organization and intersegmental spatiotemporal coordination using Electromagnetic Articulometry recordings from seven speakers of American English (henceforth, English). Whereas previous work on English has focused on word-initial clusters (preceding a vowel whose identity was not systematically varied), the present work examined word-medial clusters /pl, kl, sp, sk/ in the context of three different vowel heights (high, mid, low). Our results provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The development of research methods which have allowed us to directly observe articulatory movement with high temporal resolution has made this a tractable problem. Recent work by Shaw and colleagues has demonstrated, through a number of case studies, that coordination relations between gestures can be revealed by studying the structure of temporal variation in articulatory kinematic data (e.g., Gafos et al, 2014;Shaw, 2022;Shaw & Gafos, 2015;Shaw & Kawahara, 2018b;; see also Durvasula et al, 2021;Lialiou et al, 2021;Sotiropoulou & Gafos, 2022). A topic that is nevertheless still under-explored is how consonant clusters created via vowel deletion are coordinated, a gap that the current paper attempts to address.…”
Section: General Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…The development of research methods which have allowed us to directly observe articulatory movement with high temporal resolution has made this a tractable problem. Recent work by Shaw and colleagues has demonstrated, through a number of case studies, that coordination relations between gestures can be revealed by studying the structure of temporal variation in articulatory kinematic data (e.g., Gafos et al, 2014;Shaw, 2022;Shaw & Gafos, 2015;Shaw & Kawahara, 2018b;; see also Durvasula et al, 2021;Lialiou et al, 2021;Sotiropoulou & Gafos, 2022). A topic that is nevertheless still under-explored is how consonant clusters created via vowel deletion are coordinated, a gap that the current paper attempts to address.…”
Section: General Backgroundmentioning
confidence: 92%
“…There may be several relevant considerations for predicting which clusters are more likely reorganize than others (cf. Gafos et al, 2020;Lialiou et al, 2021). Since, in the case at hand, we are dealing with consonants that cross a syllable boundary, e.g., [ϕ.so] vs.[ϕ.ta] syllable contact constraints are one consideration (Gouskova, 2004;Murray & Vennemann, 1983;Vennemann, 1988).…”
Section: Theoretical Landscape: What Happens To Coordination When a V...mentioning
confidence: 99%